Pengaruh Jumlah Wisatawan Mancanegara, Tingkat Pengangguran Terbuka (TPT), dan Konsumsi Rumah Tangga Terhadap Pertumbuhan Ekonomi di Minahasa Utara - Cequentia Lumentut; Josep Bintang Kalangi; Steeva Y. L Tumangkeng (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Economic growth in North Minahasa is a continuous increase in the total value of goods and services produced in the region over a period of time. In a simpler context, this means improving the economic welfare of the people of North Minahasa through increased production and income. The purpose of this study is to determine the relationship between the number of foreign tourists, the open unemployment rate (TPT), and household consumption on economic growth in North Minahasa Regency. The analysis method used is a multiple linear regression model. The result of this study is that the number of foreign tourists in North Minahasa has a positive and statistically significant relationship with economic growth in North Minahasa. The open unemployment rate in North Minahasa has a positive but not statistically significant relationship with economic growth in North Minahasa. Household consumption in North Minahasa has a positive and statistically significant influence on economic growth in North Minahasa.